CULTURAL DA‘WAH IN THE MAPPATEKE ONGROANG TRADITION OF THE TO DAKKA COMMUNITY IN POLEWALI MANDAR REGENCY - Nurdin nurdin; Hariadi Hariadi; Awaludin Awaludin; Muhammad Arif; Muhammad Hasbi (Balai Penelitian dan Pengembangan Agama Makassar, 2026)
The Mappateke Ongroang tradition (swing-raising ceremony) practiced by the To Dakka ethniccommunity in Polewali Mandar Regency represents a form of cultural da‘wah that integrates Islamicteachings with local cultural values. This study addresses the tendency to view local traditions asoutdated practices incompatible with religious teachings. Using a qualitative descriptive approach witha field research design, the study explores the social realities of the tradition through direct observationand interaction with community members. The findings show that Mappateke Ongroang reflects theacculturation of Islam and local tradition. The preservation of ancestral customs infused with religiousvalues demonstrates that local culture and Islam need not be positioned in opposition. Socially, thetradition embodies humanitarian and communal values, while theologically, traditions that do notcontradict Islamic teachings remain worthy of preservation. The tradition also actualizes the values ofukhuwah (basyariah, wathaniah, Islamiyah) and social solidarity through practices such as mepposipulung (communal gathering) and mabbagi barakka (food sharing). Rituals including animalslaughtering, Barzanji recitation, hair-cutting ceremonies, and name-giving express gratitude whilereinforcing the Islamic identity of the To Dakka community. This phenomenon demonstrates that Islamcan adapt to local culture without losing the substance of its teachings. Therefore, the tradition functionsas an effective medium of cultural da‘wah that preserves the ancestral heritage of the ToDakka community while remaining widely accepted in society.